Lithium–Sulfur Batteries: A Toolbox for Lithium–Sulfur Battery Research: Methods and Protocols (Small Methods 7/2017). Issue 7 (July 2017) - Zhang, Ge; Zhang, Ze‐Wen; Peng, Hong‐Jie; Huang, Jia‐Qi; Zhang, Qiang
Abstract : Lithium–sulfur (Li–S) batteries are promising high energy density energy‐storage systems for powering electrical vehicles and unmanned aircraft. In article number1700134, Qiang Zhang and co‐workers summarize the advancements in the tools and protocols for studying Li–S batteries. Equipped with this comprehensive toolbox, researchers will be able to explore deeper and further into the cave of Li–S chemistry and paint its landscape.